Central Nervous System Toxoplasmosis in the Setting of Mycophenolate Mofetil Monotherapy for Autoimmune Hepatitis - Sathish Krishnan MD, FCCP; Vijaya Sivalingam Ramalingam MD, FCCP; Anam Naumaan MD (Journal of Investigative Medicine High Impact Case Reports)
Central nervous system (CNS) toxoplasmosis is a life-threatening opportunistic infection most often reported in patients with HIV/AIDS and solid organ transplantation. Its occurrence in immunocompetent patients is rare and even less commonly reported in those receiving single-agent immunosuppressive therapy. We present a unique case of CNS toxoplasmosis in a 68-year-old seropositive female with autoimmune hepatitis maintained on long-term mycophenolate mofetil (MMF) monotherapy. She presented with a 2-day history of confusion and expressive aphasia, without fever or focal neurologic deficits. Brain MRI revealed multiple ring-enhancing lesions, prompting a broad differential diagnosis including malignancy, abscess, and demyelination. A stereotactic biopsy confirmed necrotic tissue harboring Toxoplasma gondii tachyzoites and cysts. Her serum Toxoplasma IgG was markedly elevated, indicating reactivation rather than primary infection. Treatment with high-dose sulfamethoxazole-trimethoprim led to radiologic and clinical improvement. MMF was discontinued, and the patient remained stable off immunosuppression under close hepatic monitoring. This case underscores the underestimated risk of opportunistic infections associated with chronic MMF monotherapy in non-HIV, nontransplant populations. As similar cases begin to emerge in the literature, clinicians must recognize that MMF can sufficiently impair immune defenses to permit CNS toxoplasmosis. This report contributes to a growing body of evidence advocating for broader awareness of atypical presentations of opportunistic neuroinfections in autoimmune disease management.